2015
DOI: 10.1016/j.eururo.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Health Economic Changes as a Result of Implementation of Targeted Therapy for Metastatic Renal Cell Carcinoma: National Results from DARENCA Study 2

Abstract: In this nationwide study, we found changes in the pattern of health care costs for patients with metastatic kidney cancer after implementation of targeted therapy compared to an immunotherapy control period; however, total health care costs and income from employment were without significant changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…In a Danish study, outpatient visits and inpatient hospitalisations were estimated to cost respectively 14,308€ and 11,899€ per patient per year. The Mean annual cost per patient for outpatient hospitalisations in our study was considerably lower than the estimated costs in the Danish study [ 8 ]. These differences might be explained by differences in health resource utilisation and related DRG tariffs between the two countries.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In a Danish study, outpatient visits and inpatient hospitalisations were estimated to cost respectively 14,308€ and 11,899€ per patient per year. The Mean annual cost per patient for outpatient hospitalisations in our study was considerably lower than the estimated costs in the Danish study [ 8 ]. These differences might be explained by differences in health resource utilisation and related DRG tariffs between the two countries.…”
Section: Discussioncontrasting
confidence: 68%
“…Indeed, overall survival has improved from 13 months to 16 months with the use of targeted therapies as compared to the use of cytokine based treatments [ 6 ]. Most of these therapeutic innovations are orally administered, which modifies the management of mRCC [ 7 , 8 ]. A Danish study showed a shift in the costs of managing mRCC patients with a decrease of inpatient costs and an increase of outpatient costs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that implementation of targeted therapy did not lead to an increase in total health care costs per patient per treatment year compared with a pre-TKI era [ 25 ]. However, we have also previously shown that patients in IMDC poor prognostic group had limited OS benefit from treatment [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness of TTs in the mRCC setting has been evaluated using clinical trial data 13,14. A number of studies have confirmed the survival benefits of TTs in patients with mRCC in clinical practice1523 and one study estimated the cost impact of TTs in a national cohort of patients with mRCC;11 however, to the best of our knowledge, no studies have estimated the cost-effectiveness of TTs using real-world data. Given the limited trial data evidence of overall survival gains and uncertain external validity of randomized clinical trials, real-world cost-effectiveness analyses may provide important information for clinicians and payers on the value of TTs in the treatment of patients with mRCC and, in turn, facilitate improved decision-making and resource allocation.…”
Section: Introductionmentioning
confidence: 99%